2013
DOI: 10.1152/ajpendo.00620.2012
|View full text |Cite
|
Sign up to set email alerts
|

Developmental androgen excess programs sympathetic tone and adipose tissue dysfunction and predisposes to a cardiometabolic syndrome in female mice

Abstract: Among women, the polycystic ovarian syndrome (PCOS) is considered a form of metabolic syndrome with reproductive abnormalities. Women with PCOS show increased sympathetic tone, visceral adiposity with enlarged adipocytes, hypoadiponectinemia, insulin resistance, glucose intolerance, increased inactive osteocalcin, and hypertension. Excess fetal exposure to androgens has been hypothesized to play a role in the pathogenesis of PCOS. Previously, we showed that neonatal exposure to the androgen testosterone (NT) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
59
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 57 publications
5
59
0
1
Order By: Relevance
“…25 , 26 Excess prenatal androgens (PNA) during this period induce a hypertensive phenotype in adulthood that is characterized by impaired blood flow in the vascular endothelium 12 , increased blood volume 27 , and increased blood pressure in adult females and males. 28 , 29 However, the mechanism by which androgens induce this hypertension is not clear. Interestingly, studies of microbial transplantation have demonstrated that the microbiome affects blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…25 , 26 Excess prenatal androgens (PNA) during this period induce a hypertensive phenotype in adulthood that is characterized by impaired blood flow in the vascular endothelium 12 , increased blood volume 27 , and increased blood pressure in adult females and males. 28 , 29 However, the mechanism by which androgens induce this hypertension is not clear. Interestingly, studies of microbial transplantation have demonstrated that the microbiome affects blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…When these mice matured, we compared female mice exposed to neonatal testosterone (NTF) with control females (CF), control males (CM), and male mice exposed to neonatal testosterone (NTM). [6][7][8] Importantly, littermate males and females were androgenized at the same time, thereby facilitating comparison of their phenotypes in adulthood.…”
mentioning
confidence: 99%
“…7 showed increased and dysfunctional white adipose tissue with an increased number of enlarged and insulin resistant adipocytes as well as hypoadiponectinemia. They also displayed bone dysfunction with decreased undercarboxylated and active osteocalcin.…”
mentioning
confidence: 99%
See 2 more Smart Citations